2022
DOI: 10.21608/adjg.2022.103757.1445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biostimulation on Response of Immature Teeth with Necrotic Pulp and Apical Periodontitis to Regenerative Endodontic Therapy in Immature Dogs Teeth

Abstract: Purpose: This study was carried out to evaluate the effect of biostimulation on the regenerative response of immature teeth with necrotic pulp and apical periodontitis in dogs. Materials and Methods: Seventy-two root canals were employed in the present study as follows: Sixty root canals for experimental groups and twelve as positive and negative controls. After the induction of pulp necrosis and apical periodontitis, roots were divided into two groups, group I: Regenerative Endodontic Therapy (RET) with subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…57,58 The results of an animal study revealed the beneficial effects of laser therapy on root maturation and hard tissue formation in dogs subjected to RET with subsequent biostimulation compared to the group that did not get biostimulation treatment. 51 LLLT also proved effective in activating growth factors in laboratory and animal experiments. 50 Most studies in the field of laser application in RET are case reports and case series with only a few clinical trials.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…57,58 The results of an animal study revealed the beneficial effects of laser therapy on root maturation and hard tissue formation in dogs subjected to RET with subsequent biostimulation compared to the group that did not get biostimulation treatment. 51 LLLT also proved effective in activating growth factors in laboratory and animal experiments. 50 Most studies in the field of laser application in RET are case reports and case series with only a few clinical trials.…”
Section: Discussionmentioning
confidence: 96%
“…This work demonstrated the impact of lasers on regenerative treatments through the stimulation of growth factors. The effect of biostimulation on the pulp regeneration of immature dog teeth was investigated by Fouad et al 51 Sixty root canals were assigned to two experimental groups. Group 1 underwent disinfection by double antibiotic paste (DAP) and was then subjected to biostimulation.…”
Section: Laser Applications In the Second Step Of Ret: Tissue Enginee...mentioning
confidence: 99%
“…This shows that the removal of the etiological variables induced gradual healing of the periapical lesion. In contrast, the positive control group experienced a significantly higher level of inflammation as a result of the generated infection’s development and absence of therapy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…is is opposed by the concept of repair, which only restores functionality through scar formation or tissue remodeling. Studies have shown RET to be e ective in promoting healing and root development in immature teeth [3], and it may also be bene cial in mature teeth with chronic periapical lesions [4]. However, the extent to which RET can achieve true regeneration of the pulp-dentin complex is still under debate.…”
mentioning
confidence: 99%